Asisoasi Pergeseran Leksikon dalam Tuturan Masyarakat Pesisir di Jepara - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This study of the lexicon and the cultural values contained in the lexicon 'pergi' in the Javanese dictionary. The purpose of this study was to identify the Javanese lexicon for the mention of lexicon 'pergi ' and the function of the speech in the coastal communities of Jepara. The approach used is phenomenological context with the semantic anthropology. The data obtained was conducted by in-depth interviews with representatives of the coastal communities of Jepara. The results of this study were the lexicon variations 'pergi' in the coastal communities of Jepara. Cultural heritage in the form of language is realized through the lexicon 'pergi', such as minggat, menyang, budal, tindak, lunga, kesah, mbedal, mlancong, menyat. The 'pergi' lexicon in Javanese has explicit and implied meaning. The anthropological meaning of the 'pergi' lexicon is distinguished by: (1) the context, (2) the speech partner, (3) the mastery of the language of the speaker and the speech partner, and (4) the level of education of the speaker and partner.